Relationship Of Malaria In Pregnant Women To Anemia Events In Poriaha Puskesmas, Central Tapanuli Regency In 2020 - Lely Desi Uli Basana; Friska Apriani Sihombing; Angeli (Science Midwifery, 2020)
Anemia is the presence of malaria infection during pregnancy. The purpose of this study was to determine the relationship between malaria infection and the incidence of anemia in pregnant women using Riskesdas data in 2018. The design of this study used a cross-sectional design with the number of samples that met the inclusion and exclusion criteria in this study as many as 390 respondents. Bivariate data analysis using chi-square test and multivariate risk factor model using multiple logistic regression. Univariate results showed that 38.8% of pregnant women in Indonesia had anemia. The bivariate results of this study showed a significant relationship between malaria infection (p-value; 0.015), maternal age (p-value ; 0.046), nutritional status (p-value ; 0.005), gestational age (trimester 3 (p-value ; 0.001), 2nd trimester (p-value ; 0.005), blood tablet compliance (p-value ; 0.142), educational status (p-value ; 0.466), employment status (0.006), residence status (p-value ; 0.719 ) with the incidence of anemia in pregnant women in Indonesia based on Riskesdas data in 2018. The results of multivariate analysis showed that there was a significant relationship between malaria infection and the incidence of anemia in pregnant women after controlling for age, nutritional status, and gestational age (PR: 4.065 95%CI (1,310 -12,616). Pregnant women are expected to consume a balanced nutritious diet that is high in protein and iron from both animal (heme) and plant/vegetable (non-heme) sources, conduct ANC visits at least 4 times during pregnancy as an effort early detection of incidents ian anemia and other diseases.